2020
DOI: 10.1002/asia.201901689
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of a Near‐infrared Fluorescence Probe for Ca2+ Based on Phosphorus‐substituted Rhodamines Utilizing Photoinduced Electron Transfer

Abstract: Fluorescence imaging in the near‐infrared (NIR) region (650–900 nm) is useful for bioimaging because background autofluorescence is low and tissue penetration is high in this range. In addition, NIR fluorescence is useful as a complementary color window to green and red for multicolor imaging. Here, we compared the photoinduced electron transfer (PeT)‐mediated fluorescence quenching of silicon‐ and phosphorus‐substituted rhodamines (SiRs and PRs) in order to guide the development of improved far‐red to NIR flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…37−39 Chan and co-workers developed an ALDH1A1-responsive turn-on green fluorescence probe whose fluorescence off−on nature is controlled by photoinduced electron transfer (PeT). 37 However, because the fluorescence off−on nature in the DR/NIR region is theoretically difficult to control through PeT, 15,40 there are no examples of turn-on fluorescence probes working in the DR/NIR region. A new method for controlling the nature of off−on fluorescence based on ALDH1A1-mediated transformation is required to develop DR/NIR turn-on fluorescence probes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…37−39 Chan and co-workers developed an ALDH1A1-responsive turn-on green fluorescence probe whose fluorescence off−on nature is controlled by photoinduced electron transfer (PeT). 37 However, because the fluorescence off−on nature in the DR/NIR region is theoretically difficult to control through PeT, 15,40 there are no examples of turn-on fluorescence probes working in the DR/NIR region. A new method for controlling the nature of off−on fluorescence based on ALDH1A1-mediated transformation is required to develop DR/NIR turn-on fluorescence probes.…”
mentioning
confidence: 99%
“…In contrast, “turn-on” fluorescence probes, which reveal their fluorescence signal in response to a specific analyte, avoid the background signal of fluorescence probes from nontarget areas, leading to high-contrast imaging in vitro and in vivo. Turn-on probes can be developed by utilizing ALDH1A1-mediated transformation of an aldehyde into a carboxylate. Chan and co-workers developed an ALDH1A1-responsive turn-on green fluorescence probe whose fluorescence off–on nature is controlled by photoinduced electron transfer (PeT) . However, because the fluorescence off–on nature in the DR/NIR region is theoretically difficult to control through PeT, , there are no examples of turn-on fluorescence probes working in the DR/NIR region. A new method for controlling the nature of off–on fluorescence based on ALDH1A1-mediated transformation is required to develop DR/NIR turn-on fluorescence probes.…”
mentioning
confidence: 99%
“…Recent advancements in aminopeptidase probes, particularly those based on HMRG and 2MeSiR, are showing significant promise in improving cancer detection and monitoring as disease biomarkers ( 90 , 91 ). These probes offer distinctive advantages, such as rapid activation and reduced background signals.…”
Section: Discussionmentioning
confidence: 99%
“…In 2020, Urano and coworkers proposed that reducing the difference of energy level between the LUMO of the fluorophore and the HOMO of the chelator can effectively improve the efficiency of PeT. [24] They performed density functional theory (DFT) calculations to predict calculated the HOMO and LUMO energy levels of SiR, phosphorus-substituted rhodamine (PR), and phenylphosphorus-rhodamine (PPhR) and found that PR has the lowest LUMO among the three. In subsequent experiments, CaPR-1 (compound 12 in Figure 1c) presented the highest turn-on ratio as 5.8 folds.…”
Section: Indirect Fusion Of the Chelator To The Fluorophore Structurementioning
confidence: 99%